2022
DOI: 10.3324/haematol.2021.280501
|View full text |Cite
|
Sign up to set email alerts
|

The use of hydroxyurea pretreatment in chronic myeloid leukemia in the current tyrosine kinase inhibitor era

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A recent study suggested that undetectable transcript levels by droplet digital PCR predicts TFR success. 48 While digital PCR can reach up to 6 log reduction depth, the PCR assay used in the central lab for the present study had a limit of detection of 5.5 log reduction. We indirectly confirmed this finding as the absence of detectable BCR::ABL1 transcript levels below 5.5 log reduction was associated with a higher chance of TFR success.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A recent study suggested that undetectable transcript levels by droplet digital PCR predicts TFR success. 48 While digital PCR can reach up to 6 log reduction depth, the PCR assay used in the central lab for the present study had a limit of detection of 5.5 log reduction. We indirectly confirmed this finding as the absence of detectable BCR::ABL1 transcript levels below 5.5 log reduction was associated with a higher chance of TFR success.…”
Section: Discussionmentioning
confidence: 75%
“…Those patients with any detectable transcript levels between MR4 and MR5.4 ( n = 6) showed a 0% TFR2 rate at 6 months, while those with undetectable transcript levels (5.5 log reduction or deeper; n = 28) had a 28.6% TFR2 rate at 6 months ( p = 0.047, HR 2.759). A recent study suggested that undetectable transcript levels by droplet digital PCR predicts TFR success 48 . While digital PCR can reach up to 6 log reduction depth, the PCR assay used in the central lab for the present study had a limit of detection of 5.5 log reduction.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, the in vitro ubiquitin experiment demonstrates that RRM2 is degraded by Cdh1‐mediated polyubiquitination in G2/M phase 28 . Several RRM2 inhibitors have been used in clinical practices or trials, such as hydroxyurea, triapine, and GTI2040 29–32 . However, these drugs have not been clinically applied to NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…28 Several RRM2 inhibitors have been used in clinical practices or trials, such as hydroxyurea, triapine, and GTI2040. [29][30][31][32] However, these drugs have not been clinically applied to NSCLC. Therefore, there is an urgent need to explore more potential targets that regulate RRM2 protein level or function.…”
Section: Discussionmentioning
confidence: 99%